Characterization of Agar and Glycerin Phantoms for Generation of Stoneley Waves - Espindola-Rojas, D (IEEE Computer Society, 2025)
Surface waves can propagate at interfaces formed by two solids (Stoneley waves) only if the solids have specific mechanical properties. In particular, for an interface formed by two incompressible soft solids, they need to have different densities and similar shear wave speeds to enable the propagation of Stoneley waves. However, phantoms used in medical ultrasound typically have densities very close to that of water, since most of these materials are polymers dissolved in water. Here, we describe a recipe based on glycerin as an additive to control the density of agar-based phantoms. We have characterized the density, shear wave speed, and sound speed as a function of the proportion between glycerin, agar, and water. Our results indicate that the percentage of glycerin increases the density and the sound speed linearly and increases the shear wave speed in a quasi-linear manner. On the other hand, the concentration of agar only increases the shear wave speed. We have used these results to demonstrate the possibility of propagating Stoneley waves at interfaces made of these phantoms. © 2025 IEEE.